An assessment of the impact of Zimbabwe's mining policy legislative and institutional framework on acquisition and oversight on diamond mining rights - Gerber, Leonardus J. (University of Pretoria, 2017)
Mini Dissertation (LLM)--University of Pretoria, 2017.